Are genetic markers of interest for economic research? - Steven F. Lehrer; Weili Ding (IZA Journal of Labor Policy, 2017)
The idea that genetic differences may explain a multitude of individual-level outcomes studied by economists is far from controversial. Since more datasets now contain measures of genetic variation, it is reasonable to postulate that incorporating genomic data in economic analyses will become more common. However, there remains much debate among academics as to, first, whether ignoring genetic differences in empirical analyses biases the resulting estimates. Second, several critics argue that since genetic characteristics are immutable, the incorporation of these variables into economic analysis will not yield much policy guidance. In this paper, we revisit these concerns and survey the main avenues by which empirically oriented economic researchers have utilized measures of genetic markers to improve our understanding of economic phenomena. We discuss the strengths, limitations, and potential of existing approaches and conclude by highlighting several prominent directions forward for future research.
Keywords: I12; J19; I26; 330; Genetic markers; Gene-environment interactions; Genome-wide association studies; Candidate genes; Genetic instruments; Within-family variation